"It's almost impossible to buy a dumb TV" Experiences of automated decision-making and smart technologies in low-income homes. (March 2022) - Kennedy, Jenny; Holcombe-James, Indigo
Highlights: Shows contradictions in dominant narratives of smart home users and digital inclusion. Translates the relationship between smart home technologies and digital skills. Illustrates subversive tactics by users of automated platform and streaming services. Highlights diverse outcomes of smart hometechnologies for low-income households. Abstract: This article draws on empirical survey and interview data to investigate how smart and automated technologies are being experienced by a cohort of low-income households. The data was collected as part of a research project evaluating a program which aims to address digital disadvantages experienced by low-income households in the Shepparton area of regional Australia. The program provided a sample of students between the ages of 15 to 18 a laptop and their household's free access to unlimited broadband internet for up to two years. The digitally excluded are typically framed as lacking in abilities and access (Thomas et al., 2019 ), and as those for whom the costs of digital inclusion are too high to achieve (Ogle and Musolino, 2016; Ogle, 2017 ). Rarely, if ever, are those in low income households or those considered to be digitally marginalised imagined to also live in smart homes. Using experiences described in our data, we show how the uses of smart home technologies in these low-income households fit and contradict current understandings of both smart homes and digital inclusion; and contribute understandings of how those in low-income households experience automated technologies through the intersection of social and economic infrastructures.